Suggestion in traditional and civilized upbringing in USA and USSR - Nelly Romanova, Nadezhda Subbotina, Darima Burmenskaya, Yuliya Ivanova, (Opción, 2019)
The paper looks upon the process of upbringing from the perspective of correlation of suggestion and explanation. The methodological basis of the research was the ideas, the works of Russian philosophers, psychologists, teachers and anthropologists in the field of the theory of cognition and the theory of education. As a result, the upbringing of children in pre-civilized society was based exclusively on suggestion. In conclusion, the task of teachers, psychologists and parents is, therefore, to find a reasonable balance between traditional and civilized methods of upbringing in the family and at school.